Rapid Calorimetric Detection of Bacterial Contamination: Influence of the Cultivation Technique - Fricke, Christian; Harms, Hauke; Maskow, Thomas (Frontiers in Microbiology, 2019)
Modern isothermal microcalorimeters (IMC) are able to detect the metabolic heat of bacteria with an accuracy sufficient to recognize even the smallest traces of bacterial contamination of water, food and medical samples. The modern IMC techniques are often superior to conventional detection methods in terms of the detection time, reliability, labor and technical effort. What is missing is a systematic analysis of the influence of the cultivation conditions on calorimetric detection. For the acceptance of IMC techniques, it is advantageous if already standardized cultivation techniques can be combined with calorimetry. Here we performed such a systematic analysis using Lactobacillus plantarum as a model bacterium. Independent of the cultivation techniques, IMC detections were much faster for high bacterial concentrations (> 102 CFU·mL-1) than visual detections. At low bacterial concentrations (< 102 CFU·mL-1), detection times were approximately the same. Our data demonstrate that all kinds of traditional cultivation techniques like growth on agar (GOA) or in agar (GIA), in liquid media (GL) or on agar after enrichment via membrane filtration (GF) can be combined with IMC. The order of the detection times was GF < GIA ≈ GL ≈ GOA. The observed linear relationship between the calorimetric detection times and the initial bacterial concentrations can be used to quantify the bacterial contamination. Further investigations regarding the relation between filling level (in mm) of the calorimetric vessel and the specific maximum heat flow (in µW·g-1) illustrated two completely different results for liquid and solid media. Due to the better availability of substrates and the homogeneous distribution of bacteria growing in a liquid medium, the volume-related maximum heat flow was independent on the filling level of the calorimetric vessels. However, in solid medium the volume-related maximum heat flow approached a threshold and achieved a maximum at low filling volumes. This fundamentally different behavior can be explained by the spatial limitation of the growth of bacterial colonies and the reduced substrate supply due to diffusion.